PENINGKATAN HASIL BELAJAR BAHASA INDONESIA PADA MATERI MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN METODE PEMBELAJARAN COOPERATIVE : PROBLEM BASED LEARNING ( PBL ) PADA SISWA KELAS XI TKR 1 SEMESTER GASAL SMK NEGERI 4 KENDAL TAHUN PELAJARAN 2017/2018 - Utari Tri Hartati (Majalah Ilmiah Inspiratif, 2021)
Improved Indonesian Language Learning Outcomes in Writing Explanatory Text Using Cooperative Learning Methods: Problem Based Learning (PBL) in Class XI TKR 1 Odd Semester Students of SMK Negeri 4 Kendal in 2017/2018 Academic Year. The purpose of this study was to determine whether or not the learning outcomes increased in class XI TKR 1 Odd Semester SMK Negeri 4 Kendal in Indonesian language lessons with the subject matter of writing explanatory text. The research subjects of class XI TKR 1 SMK Negeri 4 Kendal Odd Semester 2017/2018 academic year with a total of 34 students with two cycles and each cycle consisting of 4 stages, namely: planning, action, observation, and reflection. The method of collecting research data is through observation and tests. While the research indicators are the completeness of individual learning outcomes and classical learning outcomes. Based on the results of data analysis and discussion, it was obtained that the individual learning completeness of the research subjects from the pre-cycle was 56%. From cycle I to cycle II there was also an increase in individual learning completeness, from 74% in cycle I to 91% in cycle II. Thus, from pre-cycle to cycle II, individual learning completeness increased by 35%. This also increased in classical learning completeness, namely 71% in pre-cycle to 83% in cycle II, which means an increase of 12%. Kata Kunci : Cooperative,Problem Based Learning (PBL), Menulis Teks Eksplanasi